The Awareness–Behaviour Paradox: Media Literacy and Social Media Risk Behaviour Among Nigerian Undergraduates - James Patience Ada (International Journal of Behavioral Sciences, 2026)
Background: The proliferation of internet-capable devices and social media platforms has created an intricate web of risks for Nigerian undergraduates, including cyberbullying, addiction, misinformation, and exposure to indecent content. While media literacy has been widely proposed in Western scholarship as a sustainable intervention for responsible online behaviour, its protective mechanisms remain insufficiently understood in non-Western contexts, particularly with respect to the psychological pathways through which literacy operates. Objectives: This study examined the impact of media literacy on the mitigation of risks associated with social media use among university students in Oyo State, Nigeria. Specifically, it investigated patterns of social media use, levels of media, news, and social media literacy, social media risk behaviour, and the mediating roles of self-efficacy and cognitive needs in the literacy–risk behaviour relationship. Methods: A cross-sectional quantitative survey design was adopted. A structured electronic questionnaire was administered to 391 valid respondents drawn from Ladoke Akintola University of Technology (LAUTECH) and the University of Ibadan (UI) during the 2024/2025 academic session using probability proportionate to size sampling. Data were analysed using descriptive statistics, simple linear regression, and Hayes' PROCESS macro for mediation analysis. Results: Respondents exhibited habitual and compulsive social media engagement, with WhatsApp dominant for both content-sharing and news consumption. Students demonstrated strongest proficiency in news literacy, intermediate social media literacy, and weakest general media literacy. A significant awareness–behaviour gap was identified: all three literacy dimensions positively and significantly predicted self-efficacy and cognitive needs, and both mediators were positively associated with social media risk behaviour. Five of six mediation hypotheses revealed unexpected positive partial mediation, indicating that higher literacy indirectly increases risk exposure through elevated self-efficacy and cognitive engagement. Conclusions: Media literacy, as naturally developed through informal digital engagement, does not mitigate social media risk behaviour. On the contrary, higher literacy was associated with greater risk exposure via an "awareness–behaviour paradox." Genuine risk mitigation requires deliberate instruction in self-regulation, ethical digital conduct, and algorithmic awareness beyond technical skills.
Keywords: Cognitive Needs; Nigeria; Oyo State; Self-Efficacy; Social Media Risks; University Students; media literacy